A #Co-Teaching Story from the Digital Pedagogical Framework - Alexandra Cotoc; Ioana Mudure-Iacob (Linguaculture)
The pairing of educational technology and pedagogy within new media in the exploration of foreign language teaching approaches reveals a proximity to genuine interaction among learners through immersion in language education and new media content creation. Shifting from the role of “learning to create” into a more “creating to learn”-focused role, students are empowered to become active media creators while using language and tech savviness, as well as digital apps and tools, as core skills. In doing so, the language class gains the potential to become a microcommunity of practice that encourages critical thinking and collaboration abilities while engaging in complex problem-solving skills, extending its utility into the facilitation of autonomous learning contexts. With language learners stimulated by new media in their communicative practice, it is the role of teachers to find an innovative and digital pedagogical method of matching the students’ Netspeak needs to promote cognitive activation in the EAP class. The purpose of the current study is to showcase a tested example of how educational digital pedagogy within the context of new media can be leveraged to enhance language learning outcomes via a digital escape room learning context for students with various learning backgrounds and in an innovative co-teaching scenario. The collaboratively designed and implemented digital escape room activity challenges language learners to solve language puzzles, create new media content, and use receptive and productive language skills to find clues and passwords, fostering collaboration and communication among learners who are motivated to make use of their transversal skills while breaking out from such a complex language activity.